Further results from DAMA/LIBRA-phase2 and perspectives - R. Bernabei; P. Belli; A. Bussolotti; V. Caracciolo; F. Cappella; R. Cerulli; C. J. Dai; A. d’Angelo; N. Ferrari; A. Incicchitti; A. Leoncini; X. H. Ma; et al. (Ядерна фізика та енергетика)
The data collected by the DAMA/LIBRA-phase2 set-up during two additional annual cycles have been analyzed, further investigating the long-standing model-independent annual modulation effect pointed out by DAMA deep underground at the Gran Sasso National Laboratory of the I.N.F.N. by using various different experimental configurations. Including the new results, the total exposure of DAMA/LIBRA-phase2 over 8 annual cycles is 1.53 t·yr and the evidence for a signal that meets all the requirements of the model-independent Dark Matter annual modulation signature is 11.8 σ C.L. in the energy region (1 - 6) keV. In the (2 - 6) keV energy interval, where data are also available from DAMA/NaI and DAMA/LIBRA-phase1, the achieved C.L. for the full exposure of 2.86 t·yr is 13.7 σ. No systematics or side reaction able to mimic this signature (i.e., to account for the whole measured modulation amplitude and to simultaneously satisfy all the requirements of the signature) has been found or suggested by anyone throughout some decades thus far. A preliminary result on the further lowering of the software energy threshold and perspectives are also mentioned.